1940
DOI: 10.1029/tr021i002p00363
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐relations in the system tellurium—silver

Abstract: The melting‐point diagram of the system tellurium—silver may be regarded as composed of two adjoining systems, (1) the system Te‐Ag2Te, and (2) Ag2Te‐Ag. In the first part of the system the liquidus curve first drops from the melting point of Te at 451°C to a eutectic located at 351°C, 33 atomic per cent Ag. From the eutectic the curve then rises toward the melting point of Ag2Te at 959°C. This portion of the curve consists of two main branches, with Ag3Te2 as the primary phase from 351°C to 465°C, and Ag2Te a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1957
1957
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…The phase diagram of the system silver-tellurium has been investigated by P61abon (41), Pellini and Quercigh (42), Chikashige and Saito (43), Koern (44), and Kracek and Ksanda (45). In addition to the compound AgaTe, which has a congruent melting (44), and Agl.~oTe (45) have been suggested.…”
Section: The System Silver-telluriummentioning
confidence: 99%
See 1 more Smart Citation
“…The phase diagram of the system silver-tellurium has been investigated by P61abon (41), Pellini and Quercigh (42), Chikashige and Saito (43), Koern (44), and Kracek and Ksanda (45). In addition to the compound AgaTe, which has a congruent melting (44), and Agl.~oTe (45) have been suggested.…”
Section: The System Silver-telluriummentioning
confidence: 99%
“…In addition to the compound AgaTe, which has a congruent melting (44), and Agl.~oTe (45) have been suggested. To clarify, the activity aAg of silver in Ag-Te "alloys" has been determined as a function of the Ag/Te ratio by measuring the emf of the cell Ag(s) ]AgI(s) I (Ag, Te)…”
Section: The System Silver-telluriummentioning
confidence: 99%
“…The analysis of the four crystals yielded 10.39 Å, 10.38 Å, 103.9 Å and 10.41 Å, respectively, averaging 10.39 Å ( Table 3). The results indicate that the petzite belongs to the low-temperature phase [9], and its crystallization temperature is lower than phase transition point 210±10°C.…”
Section: X-ray Diffraction Analysismentioning
confidence: 95%
“…Au-Ag-Te system is a very common intermetallic compound group. Previous authors have carried out extensive synthetic experiment research, which revealed the relationship among Au-Ag-Te mineral crystal chemistry, paragenetic association and the temperature under which the minerals were formed: (1) transformation temperature of the synthetic minerals: in the Ag-Te binary system the transition of hessite from lower crystal category into higher class takes place at 145±3°C [6][7][8][9]; for petzite in cubic system, the transition from low-temperature phase to hightemperature phase takes place at 210±10°C [8,10]. (2) Under heating, petzite-hessite begins to form solid solution at 250°C [10].…”
mentioning
confidence: 99%
“…Calculated phase diagrams of the Basic and Applied Research: Section I binary Ag-Te, Pb-Te and Ag-Pb systems, compared with experimental data obtained by Kracek et al, [17] Pelabon, [18] Chikashite and Saito, [19] Wobst, [20] Fay and Gillson, [21] Moniri and Pelot, [22] Gravemann and Wallbaum, [23] Kharif et al, [24] Kimura, [25] Friedrich, [26] Preckshot [27] and Kleppa [28] are shown in Fig. 1, 2 Figure 4 shows the calculated activity of Te in Ag-Te system at 1289 K superimposed with thermodynamic data obtained by Predel and Piehl.…”
Section: Binary Systemsmentioning
confidence: 99%